If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -9 + 8t = 9t Solving -9 + 8t = 9t Solving for variable 't'. Move all terms containing t to the left, all other terms to the right. Add '-9t' to each side of the equation. -9 + 8t + -9t = 9t + -9t Combine like terms: 8t + -9t = -1t -9 + -1t = 9t + -9t Combine like terms: 9t + -9t = 0 -9 + -1t = 0 Add '9' to each side of the equation. -9 + 9 + -1t = 0 + 9 Combine like terms: -9 + 9 = 0 0 + -1t = 0 + 9 -1t = 0 + 9 Combine like terms: 0 + 9 = 9 -1t = 9 Divide each side by '-1'. t = -9 Simplifying t = -9
| x(x+5)=270 | | h(6)=11 | | x-36=180 | | 13-t=16 | | -7(m+1)=-84 | | 5x+3.6=8x+12.9 | | (2x-3)-(-4)=5(x-7) | | 17=c/3 | | 5y+y=180 | | 6+x-8=12 | | -1.5u-1.7=-3.2 | | g-2/2=3/2 | | 2x-3=6x-9 | | 7-2(3x-1)+16=8x+11 | | (x^2)^2/x^2x | | 1/T=1/7t=1/9t=8 | | 3*(2*x+3)=-2(5x-6) | | (x2)^2/x^2x | | 25n^2+15n+2=0 | | 2n=40n+3 | | 16=x^2+2x | | x+(0.14)=4500 | | y=4x^2+4x-8 | | 5x(2-7x)= | | 3x-5=6(x-3) | | 2(x+4)-(5-2x)=5 | | 7n(-3+5n)+2= | | 5x^2-35x-10=0 | | 4-5x=9+8x | | 80-y=20 | | 3/8=rt2/3 | | 8(2x+3)=4 |